The Influence of Tea Total Production and Exchange Rate toward Export Volume of Indonesian Tea (Case on Export Volume of Indonesian Tea 2015-2019) - Anisa Nur Inzani; Suwardi - Suwardi; Misbakhul - Arrezqi (JOBS (Jurnal Of Business Studies), 2021)
Tea is one of Agriculture and Plantation business sector commodity that become one of Indonesia’s main export commodity and give contribution to Indonesia Gross Domestic Product until 12,72% at 2019. The aim of this study is to know the influence of the Amount of Tea Production and Exchange Rate toward Volume of Indonesian Tea Exports in period 2015-2019. The data used in this research is quantitative data. This study uses secondary data which obtained by collectiong data from some sources which relevant to this study such as Badan Pusat Statistik (BPS), Bank Indonesia, Direktorat Jenderal Perkebunan, Food and Agriculture Organization, and others. Regarding the data period, the data in this study use monthly data of Tea Production, Exchange Rate and Volume of Indonesian Tea Exports in period 2015-2019 with total 60 data in months. The study explored with multiple linier regression statistical analysis along with descriptive analysis and classical assumption test namely normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, and linierity test. The F-test stated that total production and exchange rate have significant influence simultaneously. Based on the t-Test result, it is found that total production has insignificant influence toward volume export of Indonesian tea partially. While exchange rate has partial significant negative influence toward volume export of Indonesian tea.